Harm reduction calls to action from young people who use drugs on the streets of Vancouver and Lisbon - Joana Canêdo; Kali-olt Sedgemore; Kelly Ebbert; Haleigh Anderson; Rainbow Dykeman; Katey Kincaid; Claudia Dias; Diana Silva; Youth Health Advisory Council; Reith Charlesworth; Rod Knight; Danya Fast (BMC, 2022)
Abstract Vancouver, Canada, and Lisbon, Portugal, are both celebrated for their world-leading harm reduction policies and programs and regarded as models for other cities contending with the effects of increasing levels of drug use in the context of growing urban poverty. However, we challenge the notion that internationally celebrated places like Lisbon and Vancouver are meeting the harm reduction needs of young people who use drugs (YPWUD; referring here to individuals between the ages of 14 and 29). In particular, the needs of YPWUD in the context of unstable housing, homelessness, and ongoing poverty-a context which we summarize here as "street involvement"-are not being adequately met. We are a group of community and academic researchers and activists working in Vancouver, Lisbon, and Pittsburgh. Most of us identify as YPWUD and have lived and living experience with the issues described in this comment. We make several calls to action to support the harm reduction needs of YPWUD in the context of street involvement in and beyond our settings.